Androgens Contribute to Sex Differences in Myocardial Remodeling under Pressure Overload by a Mechanism Involving TGF-β - Montalvo, Cecilia (Public Library of Science, 2012)
BACKGROUND: In clinical studies, myocardial remodeling in aortic valve stenosis appears to be more favorable in women than in men, even after menopause. In the present study, we assessed whether circulating androgens contribute to a less favorable myocardial remodeling under pressure overload in males. We examined sex-related differences in one-year-old male and female mice. Whereas male mice at this age exhibited circulating androgen levels within the normal range for young adults, the circulating estrogens in females were reduced. The contribution of gonadal androgens to cardiac remodeling was analyzed in a group of same-age castrated mice. METHODOLOGY/PRINCIPAL FINDINGS: Animals were subjected to transverse aortic constriction (TAC). Echocardiography was performed 2 weeks after TAC and myocardial mRNA levels of TGF-βs, Smads 2 and 3, collagens, fibronectin, β-myosin heavy chain and α-myosin heavy chain were determined by q-PCR. Protein detection of p-SMAD2/3 was performed by Western Blot. Histological staining of fibrosis was performed with picrosirius red and Masson's trichrome. Compared with females, males developed more severe tissue fibrosis, LV dilation and hemodynamic dysfunction. TAC-males showed higher myocardial expression levels of TGF-βs and the treatment with a neutralizing antibody to TGF-β prevented myocardial fibrosis development. Orchiectomy diminished TAC-induced up-regulation of TGF-βs and TGF-β target genes, and it also reduced fibrosis and hemodynamic dysfunction. The capability of androgens to induce TGF-β expression was confirmed in NIH-3T3 fibroblasts and H9C2 cardiomyocytes exposed to dihydrotestosterone. CONCLUSIONS/SIGNIFICANCE: Our results indicate that circulating androgens are responsible for the detrimental effects in the myocardium of older male mice subjected to pressure overload through a mechanism involving TGF-βs.